Problematika Implementasi Perjanjian Dalam Kerjasama dan Bagi Hasil Di Bengkel Las Semoyo Jaya: Sebuah Tinjauan Hukum Islam - Santoso, Lukman; Lestari, Devi Indah (Invest Journal of Sharia & Economic Law, 2021)
A cooperation is an agreement between two or more people to do business and achieve common goals. Cooperation can be necessary for human life, considering that humans are social creatures who need each other. People in various circles have practiced cooperation in various fields. In various cooperation practices, there are often deviations from the agreement when initially making cooperation. This article explores the problems of implementing the cooperation agreement at the Semoyo Jaya welding workshop in a review of Islamic law. By using a qualitative approach and field research methods. Meanwhile, for data collection, using observation and interview techniques. This research concluded that the implementation of the cooperation agreement at the Semoyo Jaya welding workshop was not following the principles and elements of the agreement, namely, not fulfilling any of the rights and obligations contained in the contract. Meanwhile, the profit-sharing does not meet one of the syirkah inan requirements because one party is arbitrary in providing profits to the other party. This research can contribute practically to the parties that carry out cooperation to fulfill the agreement's terms based on Islamic legal values.